The Use of Visual Media in Maharatah al-Kalam Learning - Safitri, Eka; Sa’dudin, Ihsan (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study presents one of the learning instruments used in teaching Arabic, namely using visual media. This visual media is used as a solution for learning Arabic in the industrial era 4.0 which is easier to receive material with visual media. In practice, this visual media research is not only on media that can be seen, but researchers see several things that must be considered in using visual media including the type of visual media to be used, the principles of its use, how to present it, the mechanism of its creation and selection visual media that can be used for learning maharatul kalam. This visual media is used so that students are more enthusiastic and educators are more able to innovate in learning maharatul kalam. There is also a research method used is a description-analysis with literature review. Among the visual media that can be used to teach maharatulkalam is images, posters, flannel boards, bulletin boards and wall clocks. The results of the study from this study indicate that in using visual-based learning media there are various kinds of rules that aim to realize learning effectiveness. The use of visual media is more interesting for students to continue the learning process because the visual influence has more impact on the ease of understanding the material. There are principles that must be considered when using visual media in learning that is prioritizing simplicity, clear and easy to read.